Name of the xerophytic communities of the Ciénaga de La Palmita, Zulia state, Venezuela - Vera, Antonio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The designation of deciduous thorny xerophytic shrublands is proposed for the plant communities xerophytic of the Ciénaga de La Palmita, Zulia state, Venezuela. The research was carried out in two areas: the southern sector of the xerophytic forest and the xerophytic enclave of the isleta El Hicacal of the Wildlife Fauna Reservoir Ciénaga de La Palmita and Isla de Pájaros.Tours, field explorations and collection of botanical samples were carried out (september 2019-february 2020) during the dry and rainy periods, and emphasis was placed on floristics, life habits and average height of individuals. The predominant biotype was the arboreal one and presented an average height of 6.5 and 7.9 m (low height) for each area respectively, thus designating the term shrublands. The xerophytic and thorny traits were present in the families with the highest number of species (Cactaceae, Euphorbiaceae, Fabaceae and Poaceae), highlighting leafless species, with aquiferous parenchyma, photosynthetic stem, thick leaf cuticles, compound leaves, thorns, spines and underground organs, giving them the qualifiers xerophilous and thorny. The term deciduous resulted from the high variety of deciduous species compared to the reports made for other communities in arid and semiarid areas of the country. The denomination of deciduous thorny xerophytic shrublands constitutes a new denomination for the studied area, appropriate to be included in the Planning and Use Regulation Plan (PORU) of said biotic space and provides precise guidance on the administration and management of the natural plant resources of this Area Under Special Administration Regime (ABRAE).